Islamic Legal and regulatory provisions for Alzheimer's patients - Al-Turki, Asma Mohammed (Journal of Islamic Sciences, 2019)
Alzheimer's is the disease of the era destroys the brain cells then affects the work and life of the patient and deteriorates gradually may lead to death after that, I liked to look for its meaning and terminology and symptoms and what the Islamic legal and legal provisions for patients, I followed in my research deductive approach, Research that Alzheimer's disease is devastating nerve causes the brain atrophy gradually and the destruction of the person's ability to learn, it has been called a number of terms of the scientists, including real dementia and cerebral dementia and mental disorders, the causes of the disease include old age and diseases of blood vessels and head injuries and has a number of types of treatments and It's also relates some of the Islamic rulings The Alzheimer's patient in the first stage applies to him the provisions of the Full-fledged person, but in the case of medium and late it passes a mixture of the provisions of madness and the ship and dementia in accordance with its provisions.
Keywords: Alzheimer's Disease; Cerebral Dystrophy; Islamic Law; Law